The Role of Notaries in Making Wills Regarding the Distribution of Inheritance according to Islamic Compilation Law - Nirwan Kusuma; Aryani Witasari; Denny Suwondo (Sultan Agung Notary Law Review, 2022)
This research aims to know and analyzing the role of a notary in making a will regarding the distribution of inheritance according to Islamic law.Analyzing the role of a Notary in making a will based on the provisions of the laws and regulations in force in Indonesia as well as the compilation of Islamic law as well as the obstacles and solutions of a notary inmaking a will regarding the distribution of inheritance according to Islamic law. This research is a type of legal research with a focus on the study of sociological juridical approach (Sociology Legal Research). Juridically by reviewing the applicable laws and regulations in accordance with the compilation of Islamic law and the Civil Code to achieve the final goal. The results of a sociological juridical study on the role of the role of a notary in making a will regarding the distribution of inheritance according to Islamic law is the role of a Notary in making a will before a Notary refers to the provisions of Article 1 point 1 UUJN which states, "Notaries are public officials who are authorized to make authentic deeds and have other authorities as referred to in this law or based on other laws", where each will or testament must be in the form of a deed in order to obtain legal certainty as a binding authentic deed. Inheritance assets often cause various legal and social problems, the obstacles that are often faced by notaries are very complex in their implementation, including: the notary lacks control and does not understand all the provisions of the inheritance certificate, the notary is not careful enough to check and ensure the completeness of the documents, the difficulty of the notary to ensure that the witnesses presented must really know about the family of the deceased heir, it is still often encountered witnesses or heirs who are dishonest in providing information and there is no legal unification regarding the regulation of the implementation of the certificate of inheritance in Indonesia. From the above constraints, the researcher draws conclusions in the form of solutions including: notaries have a role to educate to become professional and reliable notaries, namely by carrying out scientific activities such as seminars about notaries, notaries in taking an action must be prepared and based on rules applicable law, a notary must be able to observe the actual facts in the reality.